Development of Gyoza Based on Red Bean Flour, Beef, and Chicken Liver to Increase Iron Content and Economic Value: Literature Review - Made Ayu Suari Dewi (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Iron deficiency anemia remains a major nutritional challenge worldwide, especially among women of reproductive age, pregnant women, and adolescents. An emerging food-based strategy involves the fortification of red bean (Phaseolus vulgaris) products due to their high iron content. However, the bioavailability of iron from red beans is limited by antinutritional factors such as phytic acid and polyphenols. This review explores the development of functional food products, specifically gyoza formulated with red bean flour, beef, and chicken liver. The incorporation of heme iron sources like beef and chicken liver has been shown to synergistically enhance the absorption of non-heme iron. Evidence from various studies demonstrates that this formulation increases iron content, improves nutritional value, and meets sensory acceptability standards. As a culturally adaptable and economically feasible product, red bean–based gyoza with beef and chicken liver holds strong potential as an innovative dietary intervention to combat iron deficiency anemia.